Role of Culture and Media in Disability Studies: A Medium of Social Construction of Disability. (2nd January 2023) - Dawn, Ranjita
Abstract: This article attempts to review representation of disability in Indian culture with reference to Indian Religion, Literature and Cinema and the role it can play towards effective disability awareness interventions. Culture as the basis of social representation has been exerting a domineering impact on molding peoples' identities or self-representations across the globe and has more serious implications as people with disabilities may analyze their experiences in light of the existing meanings and practices prevalent in society. The article addresses the milieus of recurring themes representing disability and discourses of "normalcy" in Indian Religion, Literature and films. It argues that they play a dominant role in accentuating an inconsequential image and attitude wherein "disability" is perceived more as a punitive, dependence, disequilibrium or social misfit. The article analyzes the theoretical outlook based on the social model of disability, a perspective that includes specific analyses of the representation of people like themselves in popular culture. It is based on a systematic and thorough review of works of Indian Religion, Literature and a few Hindi films. Apart from these several books and articles have also been critically reviewed. The article strongly advocates that portrayal of people with disability need not result in characters being relegated either to an object of derision, pity, or comedy and does not necessitate a reaction of any kind, from the other "normal" characters but rather they should be used as a strong medium for raising mainstream awareness of experiences of people with disabilities.